HUBUNGAN ANTARA INTERNAL LOCUS OF CONTROL DAN DUKUNGAN SOSIAL KELUARGA DENGAN KEMATANGAN KARIR SISWA SMK X KELAS XII - Harwinia Trisanti Dewi Apriani (Jurnal Psikologi, 2017)
Objective of this research was to verify the relationship between the internal locus of controland social support from family variables with the career maturity variable among 12th gradevocational students. I proposed 3 hypotheses. Firstly, there was positive correlation betweenthe internal locus of control and the student’s career maturity. Secondly, there was positivecorrelation between the social support from family and student’s career maturity. Thirdly,there were positive relationship between those two independent variables and the careermaturity variable. The data were collected through 3 scales i.e. internal locus of control,social suppor7 from family, and career maturity. Sixty vocational students participated in thisresearch. They were recruited through the cluster random sampling technique. This researchrevealed that the first hypothesis was accepted, rxy = .639, p = .00. The second hypothesis wasalso accepted, rxy = .474, p = .00. The third hypothesis was accepted, F = 23.408, p = .00, R2 =.451. Two suggestions at the discussion session were addressed either to the G & C teacherat the vocational school or parents in order to prepare student’s career maturity readiness.Key words: Locus of control, social support from family, career maturity.